2008
DOI: 10.1103/physrevd.77.115012
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and electroweak symmetry breaking in models with warped extra dimensions

Abstract: We show that a discrete exchange symmetry can give rise to realistic dark matter candidates in models with warped extra dimensions. We show how to realize our construction in a variety of models with warped extra dimensions and study in detail a realistic model of Gauge-Higgs Unification/composite Higgs in which the observed amount of dark matter is naturally reproduced. In this model, a realistic pattern of electroweak symmetry breaking typically occurs in a region of parameter space in which the fit to the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 71 publications
3
67
0
Order By: Relevance
“…With this choice we are able to parametrize the low-energy dynamics of several explicit models proposed in the literature (see for example refs. [27,[63][64][65][66][67]). The requirement of a mixing with the elementary top quark fixes the U(1) X charge of these operators to be 2/3.…”
Section: Jhep10(2013)160mentioning
confidence: 99%
“…With this choice we are able to parametrize the low-energy dynamics of several explicit models proposed in the literature (see for example refs. [27,[63][64][65][66][67]). The requirement of a mixing with the elementary top quark fixes the U(1) X charge of these operators to be 2/3.…”
Section: Jhep10(2013)160mentioning
confidence: 99%
“…The introduction of more sets of fermionic composites is inspired by the five-dimensional model presented in [37], which does not seem to suffer from such severe constraints. In [31], it was shown that a four-dimensional composite Higgs model with two multiplets of fermionic resonances is compatible with EWPT in large regions of parameter space.…”
Section: The Fermionic Sectormentioning
confidence: 99%
“…It also features a very strong potential for the discovery or exclusion of new physics/particles, thus opening the possibility of investigating both strongly and weakly coupled extensions of the Standard Model. New vector-like (VL) fermions are often present in many of the extensions of the SM, especially in relation with the top sector (top partners, as for example in composite Higgs models [1][2][3][4], extradimensional models [5][6][7][8][9][10][11], little Higgs models [12][13][14], gauge-Higgs models [15,16], gauge coupling unification [17,18] and models with an extended custodial symmetry [19,20]). Both CMS [21] and ATLAS [22] have recently devoted a considerable effort in the analyses apt to setting bounds on this type of new particles.…”
Section: Introductionmentioning
confidence: 99%